A PROCESS FOR THE HIGH RECOVERY EFFICIENCY OF SULFUR FROM AN ACID GAS STREAM - CHEN JEN KAI; HUFFMASTER MICHAEL ARTHUR (2007)
A process for the recovery of sulfur from an acid gas stream is disclosed. The process includes a Claus sulfur recovery step in combination with a direct reduction step and a biological sulfur recovery step to provide a sweet gas stream having a very low concentration of hydrogen sulfide and sulfur dioxide. The process includes reacting an acid gas steam with oxygen under such oxidation conditions to yield a combustion gas comprising hydrogen sulfide and sulfur dioxide. The combustion gas is reacted under Claus reaction conditions to yield a reaction gas comprising sulfur. Sulfur is recovered from the reaction gas to yield a Claus tail gas comprising hydrogen sulfide and sulfur dioxide. The Claus tail gas is reacted under direct reduction reaction conditions to yield a direct reduction gas comprising sulfur. Sulfur is recovered from the direct reduction reaction gas to yield a tail gas comprising a concentration of hydrogen sulfide. The direct reduction tail gas is contacted with a lean absorbent to thereby remove from the tail gas a portion of the hydrogen sulfide contained therein and to yield a sweet gas and a rich solvent comprising dissolved hydrogen sulfide. The dissolved hydrogen sulfide of the rich solvent is biologically oxidized to elemental sulfur by contacting the rich solvent with sulfur bacteria under suitable biological oxidation conditions. ® KIPO & WIPO 2007